Ovulation induction regimens are associated with a higher rate of livebirth after frozen single-blastocyst transfer among women with polycystic ovary syndrome - Niu, Yue; Zhao, Dingying; Wang, Yuhuan; Suo, Lu; Zou, Jialin; Wei, Daimin (Frontiers in Endocrinology, 2022)
Background：Hormone replacement therapy (HRT) regimen was suggested to be associated with a decreased rate of livebirth and a higher risk of hypertensive disorders of pregnancy (HDP) after frozen cleavage stage embryo transfer in women with polycystic ovary syndrome (PCOS). With the dramatically increased use of elective single embryo transfer, there is great need to explore the impacts of different endometrial preparation regimens on frozen single-blastocyst transfer in women with PCOS. Methods：In this study, a total of 3941 women who diagnosed with PCOS and underwent single-blastocyst transfer during their first cycles of frozen embryo transfer (FET) between March 2012 and December 2020 were included. We retrospectively compared the pregnancy and neonatal outcomes after frozen single-blastocyst transfer with endometrial preparation by HRT regimen (n = 3540), ovulation induction by human menopausal gonadotropin (hMG) regimen (n = 226), and ovulation induction by letrozole regimen (n = 175). Results：After adjustment for confounders with multivariable logistic regression, the hMG regimen group [(58.4% vs. 49.6%; adjusted odds ratio (aOR): 1.43; 95% confidence interval (CI): 1.09-1.89)] and the letrozole regimen group (58.9% vs. 49.6%; aOR: 1.42; 95% CI: 1.04-1.93) were associated with a higher rate of livebirth (primary outcome), compared with the group with HRT regimen. As to the secondary outcomes, the rate of pregnancy loss in the hMG regimen group (22.8% vs. 30.3%; aOR: 0.69; 95% CI: 0.48-1.00) and letrozole regimen group (16.9% vs. 30.3%; aOR: 0.48; 95% CI: 0.30-0.78) was also lower than that in the HRT regimen group. The pregnancy outcomes between hMG regimen group and letrozole regimen group were similar. We did not observe significant difference in the incidences of maternal and neonatal complications among these three groups. Conclusion：Ovulation induction regimen with letrozole or hMG for endometrial preparation was associated with a higher livebirth rate and a lower pregnancy loss rate in frozen single-blastocyst transfer cycles among women with PCOS.